2003
DOI: 10.5628/rpcd.03.01.108
|View full text |Cite
|
Sign up to set email alerts
|

Fisiologia da fadiga muscular. Delimitação conceptual, modelos de estudo e mecanismos de fadiga de origem central e periférica

Abstract: RESUMOO tecido muscular esquelético dos mamíferos possui a capacidade de produzir níveis elevados de força quando activado. A incapacidade de produzir repetidamente no tempo um determinado nível de força ou potência muscular designa-se por fadiga neuromuscular, fenómeno que pode manifestar-se de forma aguda e que pode persistir durante dias ou mesmo semanas. A etiologia da fadiga muscular tem atraído o interesse dos investigadores desde há mais de um século. Contudo, os seus agentes e locais definitivos perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
29

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 114 publications
0
11
0
29
Order By: Relevance
“…This heavy overload induces a larger production of metabolites 18,26 and, therefore, causes a greater activation of muscular receptors sensible to biochemical disturbances, such as the afferent groups III and IV, the muscle spindles and the Golgi tendon organ [27][28][29] . Taking into account that these structures generate a sensorial feedback that reduces the recruitment capacity of the motor units 30 , it is possible that the low amplitude values of the electromyographic signal recorded during the multi-joint exercises analyzed by Augustsson et al 5 and Gentil et al 5 were due to inhibitory mechanisms initiated in the single-joint exercises. Differing from these results, the moderated loads applied in the single-joint exercise of this experiment seem not to jeopardize the recruitment of motor units in the multijoint exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This heavy overload induces a larger production of metabolites 18,26 and, therefore, causes a greater activation of muscular receptors sensible to biochemical disturbances, such as the afferent groups III and IV, the muscle spindles and the Golgi tendon organ [27][28][29] . Taking into account that these structures generate a sensorial feedback that reduces the recruitment capacity of the motor units 30 , it is possible that the low amplitude values of the electromyographic signal recorded during the multi-joint exercises analyzed by Augustsson et al 5 and Gentil et al 5 were due to inhibitory mechanisms initiated in the single-joint exercises. Differing from these results, the moderated loads applied in the single-joint exercise of this experiment seem not to jeopardize the recruitment of motor units in the multijoint exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Este fenómeno es considerado como uno de los tópicos principales dentro de la investigación en fisiología del ejercicio 2 , es decir, como un problema complejo que depende de muchos factores como el tipo, duración e intensidad del esfuerzo, tipo y densidad de las miofibrillas musculares, niveles de aptitud física individual, motivación, alimentación y condiciones ambientales 3 . Sin embargo, varios autores indican que la fatiga se manifiesta por la disminución de la fuerza muscular generada durante y después del ejercicio sub-máximo y máximo, así como también a la incapacidad de mantener una determinada intensidad de ejercicio en el tiempo, a la disminución de la velocidad de contracción y al aumento del tiempo de relajamiento muscular 4 .…”
Section: Introductionunclassified
“…It is known that the muscle tissue is able to produce strength when activated (1) . However, the incapacity of producing strength repeatedly is characterized as neuromuscular fatigue, a symptom which can last for many days or weeks (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is suggested that the decline in the 400/Post compared to the 400/C is due to neuromuscular factors which can be related to alterations of some electromyographic parameters, acting as a protective device against possible deleterious effects of the muscle fiber integrity (1) . It can be concluded from the results presented that, after the active or passive recovery the performance behavior in the 400 meters after the plyometric exercises session was similar when the two recovery methods are compared.…”
mentioning
confidence: 99%